2020
DOI: 10.1142/s021968672050016x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Reverse Logistics Barriers in Manufacturing Industry of Pakistan: An ISM and MICMAC Approach

Abstract: Due to industrialization, increasing solid waste is affecting environmental integrity globally. Reverse logistics (RL) has become a significant tool to deal with environmental degradation issues, and it is being implemented in developed countries. However, RL is at the infancy stage in developing countries especially in Pakistan due to different obstacles. This study aims to identify and analyzes the interrelationship between barriers affecting RL implementation in Pakistani manufacturing industry using an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 70 publications
0
24
0
Order By: Relevance
“…Financial and economic barriers emerged as one of the most prevalent barriers. Processes related to RL, for instance, collection and transportation, are expensive (Prakash and Barua, 2016;Waqas et al, 2020). Low profitability on account of high initial investments and operating costs and limited return on investments detriment RL adoption (Prakash and Barua, 2016).…”
Section: Barriers and Critical Success Factors To Implementing Rlmentioning
confidence: 99%
“…Financial and economic barriers emerged as one of the most prevalent barriers. Processes related to RL, for instance, collection and transportation, are expensive (Prakash and Barua, 2016;Waqas et al, 2020). Low profitability on account of high initial investments and operating costs and limited return on investments detriment RL adoption (Prakash and Barua, 2016).…”
Section: Barriers and Critical Success Factors To Implementing Rlmentioning
confidence: 99%
“…However, as Table 7 indicates, it does not feature among the top five barriers of other countries. Recent study of Waqas et al [128] mentioned that lack of enforceable laws on product return is a major barrier in reverse logistics in Pakistan manufacturing sector. Earlier studies identified the lack of financial support [57], implementation of environmental policies [58], additional cost due to green innovation as top ranked barriers to green innovation practices.…”
Section: Comparison With Other Countriesmentioning
confidence: 99%
“…Sustainable supply chain practices refer to those actions and activities that deal with the environmental, financial, and social aspects of manufacturing firms (Waqas et al 2020 ). The optimization of SSCM activities decreased the demand for reverse logistics, predominately minimizing waste generation, promoting sustainable transportation, and recycling and reusing the waste material that is the foundation for the circular economy (Lee et al 2014 ; Ranjbari et al 2021 ).…”
Section: Sustainable Supply Chain Management Technological Innovation...mentioning
confidence: 99%